The miles and snow business strategy typology and the adoption of management accounting practices / Tuan Zainun Tuan Mat, Ammar Syafiq Subri and Fadzlina Mohd Fahmi - Tuan Mat, uan Zainun; Syafiq Subri, Ammar; Mohd Fahmi, Fadzlina (Universiti Teknologi MARA, 2021)
Changes in the business environment requires that a company adopts a more adaptive strategy. A business strategy is not just about planning, but it needs to be supported with meaningful information. Management accounting complements a business strategy by providing crucial information, not just limited to cost efficiency, but customer satisfaction and quality management. However, the adoption of management accounting practices (MAPs) is believed to be influenced by strategy. Using the Miles and Snow (1978) business strategy typology model, this study examined the influence of business strategy on the adoption of MAPs, focusing on how the different types of business strategies used in organizations may influence the adoption of MAPs. Data was collected from manufacturing companies in Malaysia. The result showed that most Malaysian manufacturing companies utilized three major classifications of strategies, i.e., defender, prospector, analyzer, and only a few were classified as reactors. The result showed that the adoption level of both traditional and advanced MAPs is also high. Findings from this study indicated an influence of the defender and analyzer types towards adopting traditional MAPs, whereas the prospector type had influenced the adoption of advanced MAPs.